Econometric Analysis of Farmers Access to Agricultural Credit and Repayment in South East, Nigeria: Implications for Poverty Alleviation - M.O, Ugbajah; Amah, J.T (Advances in Social Sciences Research Journal, 2017)
The study analysed farmers access to agricultural credit and repayment in Southeast, Nigeria. The study specifically described the socioeconomic characteristics of the respondents, sources of credit awareness, and effects of socioeconomic characteristics on use and repayment of credit. Multistage and simple random sampling methods were used to select 120 respondents. Primary data were collected by means of questionnaire and 3 point likert scale. Non parametric and parametric statistical tools including frequency, distribution, percentages, mean ranking and multiple regression were deployed for data analyses majority (72%) of the respondents were married, 75% had above 11 years experience in farming, mean credit obtained was N108, 866.7 and mean amount repaid N 6405.2. the output of the multiple regression R2 of 83% with the coefficient of education, farming experience, credit awareness and interest rate were significant of the 0.05 probability level. The farmer’s access to agricultural credit should be ensured by provision of interest free credit facilities, minimizing beaucratic bottlenecks, education of farmers in proper utilization of credit and training on management and saving mobilization should be encouraged.